Free Cholesterol‐Induced Liver Injury in Non‐Alcoholic Fatty Liver Disease: Mechanisms and a Therapeutic Intervention Using Dihydrotanshinone I - Jia‐Wen Shou; Juncai Ma; Xuchu Wang; Xiao‐Xiao Li; Shu‐Cheng Chen; Byung‐Ho Kang; Pang‐Chui Shaw (Advanced Science)
Abstract Build‐up of free cholesterol (FC) substantially contributes to the development and severity of non‐alcoholic fatty liver disease (NAFLD). Here, we investigate the specific mechanism by which FC induces liver injury in NAFLD and propose a novel therapeutic approach using dihydrotanshinone I (DhT). Rather than cholesterol ester (CE), we observed elevated levels of total cholesterol, FC, and alanine transaminase (ALT) in NAFLD patients and high‐cholesterol diet‐induced NAFLD mice compared to those in healthy controls. The FC level demonstrated a positive correlation with the ALT level in both patients and mice. Mechanistic studies revealed that FC elevated reactive oxygen species level, impaired the function of lysosomes, and disrupted lipophagy process, consequently inducing cell apoptosis. We then found that DhT protected mice on an HCD diet, independent of gut microbiota. DhT functioned as a potent ligand for peroxisome proliferator‐activated receptor α (PPARα), stimulating its transcriptional function and enhancing catalase expression to lower reactive oxygen species (ROS) level. Notably, the protective effect of DhT was nullified in mice with hepatic PPARα knockdown. Thus, these findings are the first to report the detrimental role of FC in NAFLD, which could lead to the development of new treatment strategies for NAFLD by leveraging the therapeutic potential of DhT and PPARα pathway.